Determinants of Menstrual Hygiene Practices in Rural Adolescents: A Systematic Review - Siti Lomrah; Lisa Triana Arlym (GLOBAL HEALTH SCIENCE GROUP, 2024)
According to a 2017 WHO report, more than 2.3 billion women and girls worldwide face serious challenges in managing their periods. According to a UNICEF report, 10% of girls in African schools miss their periods. The limited hygiene facilities in schools, the lack of hygienic sanitary napkins, and the use of unhygienic materials make them stressed, anxious, and skip classes because they are worried about unpleasant Odors. Research shows that unhygienic practices during menstruation increase the risk of infections in the reproductive tract and genitourinary tract. The purpose of this systematic literature review is to find out what factors are obstacles for adolescents in the practice of menstrual hygiene. The research is in the form of a systematic literature review by identifying all published literature using relevant keywords. The selected articles are those published in the last 5 years which are complete texts, then selected based on titles and abstracts, which in the end found 17 articles that meet the inclusion criteria and have high quality. The low level of knowledge among the participants was seen in their unpreparedness when entering the menarche period and their strong view of menstruation as a socially taboo and can be judged by the various restrictions they have, due to strong socio-cultural beliefs and practices. So there is a relationship between age, maternal education, culture and beliefs, economic status and the practice of menstrual hygiene in adolescents. The factors hindering adolescents in practicing menstrual hygiene are interconnected. Age, maternal education, cultural and belief factors, as well as economic status, all play a role in influencing menstrual hygiene practices among adolescents.